Graphene-Based Materials in Dental Applications: Antibacterial, Biocompatible, and Bone Regenerative Properties. (7th February 2023) - Williams, A. G.; Moore, E.; Thomas, A.; Johnson, J. A.
Abstract : Graphene-based materials have been shown to have advantageous properties in biomedical and dental applications due to their high mechanical, physiochemical, antibacterial, and stem cell differentiating properties. Although graphene-based materials have displayed appropriate biocompatible properties when used in implant materials for orthopedic applications, little research has been performed to specifically test the biocompatibility of graphene for dental applications. The oral environment, compared to the body, varies greatly and must be considered when evaluating biocompatibility requirements for dental applications. This review will discuss in vitro and in vivo studies that assess graphene's cytotoxicity, antibacterial properties, and cell differentiation ability to evaluate the overall biocompatibility of graphene-based materials for dental applications. Particle shape, size, and concentration were found to be major factors that affected overall biocompatibility of graphene.